Examining the emotional dimensions of academic librarianship emerging research and opportunities - Lowe, Megan 1979-; Reno, Lindsey M. 1979- (Advances in library and information science (ALIS) book series, 2018)
"This book explores the emotional dimensions of academic librarianship. It presents concepts that provide some psychological and emotional context to help academic librarians understand their experiences and better cope with them. It also helps to mitigate the impact of the negative experiences and, when possible, prevent the problems associated with emotional exhaustion and burnout"...